2018
DOI: 10.21776/ub.jels.2018.008.01.08
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rosella Extract (Hibiscus sabdariffa) against the n-carboxymethyl-lysine, NF-κβ, TNF-α in the Rats Heating Food Diets

Abstract: The food processing by heating can increase the formation of AGEs (Advanced Glycation End Products). AGEs are compounds that formed from a non-enzymatic continuous glycation reaction between proteins and sugar residues. The CML (N-carboxymethyl-lysine) is used as a marker for AGEs cause most commonly found in vivo. The bond of AGEs and RAGE (reseptor for AGEs) induce various signaling pathways that trigger inflammation and increase oxidative stress. The AGE and RAGE interaction activate the transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Foods with certain nutritional composition and bioactive compounds are the alternative option to control or prevent disease manifestations. In vitro study showed that anthocyanin compounds in Rosella extract could reduce the levels of AGEs (n-carboxymethyl-lysine), leading to the prevention of NF-κB activation and TNF-α expression ( 11 ). Red grape skin extract was reported to decrease the levels of fructosamine, Nε-(carboxymethyl) lysine (CML), and protein oxidation effectively so that the inhibition of AGEs formation occurred ( 12 )RGSE was screened for its potential as an antioxidant using various in vitro models.Methods: Antioxidant activity was measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH.…”
Section: Introductionmentioning
confidence: 99%
“…Foods with certain nutritional composition and bioactive compounds are the alternative option to control or prevent disease manifestations. In vitro study showed that anthocyanin compounds in Rosella extract could reduce the levels of AGEs (n-carboxymethyl-lysine), leading to the prevention of NF-κB activation and TNF-α expression ( 11 ). Red grape skin extract was reported to decrease the levels of fructosamine, Nε-(carboxymethyl) lysine (CML), and protein oxidation effectively so that the inhibition of AGEs formation occurred ( 12 )RGSE was screened for its potential as an antioxidant using various in vitro models.Methods: Antioxidant activity was measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with previous study stating that anthocyanins, a type of flavonoid, can inhibit the formation of AGEs. 32 This study found that the ability of HSL to reduce RAGE levels was lower compared to quercetin. This may be due to the HSL extract used containing various compounds other than flavonoids, such as saturated and unsaturated fatty acids, proteins, carbohydrates, minerals, organic acids (citric acid, hydroxycitric acid, hibiscus flower, oxalate, and ascorbate), anthocyanins, and polysaccharides.…”
Section: Discussionmentioning
confidence: 73%
“…With the variety of contents in the HSL extract, increasing the dose also increases the activity of other ingredients, reducing the effect of flavonoids. 32 Anthocyanins are a type of polyphenol flavonoid within the antioxidant group. The mechanism by which anthocyanins are indicated as inhibitors of AGEs (Advanced Glycation End Products) formation is through inhibiting the binding of AGEs to their receptor (RAGE) and inhibiting monosaccharide auto-oxidation, preventing lipid peroxidation, and inhibiting the polyol pathway.…”
Section: Discussionmentioning
confidence: 99%